A Barotropic Model of the Red Sea Circulation. (14th June 2012) - El-Shabrawy, Mohamed M.; Fasseih, Khaled M.; Zaki, Mamdouh A.
Abstract : A linear depth-averaged numerical model of the horizontal barotropic circulation of the Red Sea is developed. The flow considered is incompressible, quasi-steady and free from vertical buoyancy currents and horizontal density currents. The model predicts general water circulation as affected by friction stresses at the irregular Red Sea bottom and coastal features, variable Coriolis force, vertical, and lateral turbulent friction, and seasonal non-uniformity of wind stress at the sea surface. The implicit finite-difference solution of the boundary value problem is verified with previous solutions for a rectangular constant-depth sea and for an elliptical lake with uniformly-sloping bottom topography. The model output is shown as plots of seasonally-averaged mass-transport vectors and circulation streamlines in the Red Sea basin.